2021
DOI: 10.1109/access.2021.3099758
|View full text |Cite
|
Sign up to set email alerts
|

Text Guide: Improving the Quality of Long Text Classification by a Text Selection Method Based on Feature Importance

Abstract: The performance of text classification methods has improved greatly over the last decade for text instances of less than 512 tokens. This limit has been adopted by most state-of-the-research transformer models due to the high computational cost of analyzing longer text instances. To mitigate this problem and to improve classification for longer texts, researchers have sought to resolve the underlying causes of the computational cost and have proposed optimizations for the attention mechanism, which is the key … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…The original Text Guide method was proposed and described in detail in [11]. Here, we provide a brief review as a context for our current experiments.…”
Section: Revisiting Text Guidementioning
confidence: 99%
See 4 more Smart Citations
“…The original Text Guide method was proposed and described in detail in [11]. Here, we provide a brief review as a context for our current experiments.…”
Section: Revisiting Text Guidementioning
confidence: 99%
“…More complex deep learning approaches described by [9,10] have proposed an encoder-decoder model or another "judge" model to select relevant sentences for the final analysis. Very recently, [11] proposed a simpler method called Text Guide, which is based on a CTC model that also allows important text fragments to be selected for text classification. However, the authors of Text Guide have indicated that the performance of their method could presumably be improved through additional experiments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations